Peran GCG dan ISR dalam Memoderasi Struktur Modal dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan - Dinda Avista Sabela; Puji Endah Purnamasari (Journal of Management and Bussines (JOMB), 2023)
The purpose of this study is to determine the role of ISR and GCG in moderating the Capital Structure proxied by DAR and DER, Company Growth (Growth) on Company Value. This research uses a quantitative method with 32 companies that are included in JII70 for the 2018-2021 period to be used as samples in this study. The technique used in sampling is using purposive sampling method. The analytical method uses Eviews 12. The results of this study include a) the DAR variable has a probability value of 0.01 with Î± = 0.05 which means less than 0.05; b) the DER variable has a probability value of 0.57 with Î± = 0.05 which means more than 0.05; c) the growth variable has a probability value of 0.29 with Î± = 0.05 which means more than 0.05. The results of the f test have a probability value of 0.003 with Î± = 0.05 which means less than 0.05. It can be concluded that partially DAR has a negative and significant effect on company value. While DER and growth have no effect on firm value. Keywords: DAR, DER, Growth, Islamic Social Reporting, Institutional Ownership